Visible-transparent and UV/IR-opaque colloidal dispersions of Ga-doped zinc oxide nanoparticles. (29th June 2016) - Trenque, I.; Gaudon, M.; Duguet, E.; Mornet, S.
Abstract : ZnO:Ga supracolloidal particles are disaggregated into transparent dispersions in the visible range and may be used as an effective UV and infrared filter. Abstract : Preliminary Mie scattering calculations show that ZnO:Ga nanoparticles dispersed in a visible-transparent matrix could create an efficient infrared barrier while remaining transparent to visible light. The ZnO:Ga supracolloidal particles elaborated by a polyol process are successfully disaggregated in the presence of an alkanethiol, leading to stable dispersions whose absorption spectra are in agreement with calculations.